PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PADA SISWA SMPN 2 KOTA JAMBI TAHUN AJARAN 2013/2014 - Risma Simamora (Jurnal Ilmiah Dikdaya, 2017)
The background of this research by the ability of students' mathematical concepts. This is due to the teachers who are more active in the learning process, whereas students only receive the material and noted that learning math is very boring for students. The population in this study were all students of class VIII except VIII class F SMPN 2 Jambi. Sampling using random sampling so that the sample drawn is VIII A and VIII B with different treatment. The results showed that the average ability students' understanding of mathematical concepts experimental class was 72.33 with a standard deviation of 6.7, and the average value of the ability of understanding mathematical concepts control class 59.75 with a standard deviation of 8.6. Based on the results of hypothesis test obtained t at 5.46 and 1.67 ttable on the real level of 0.05. From the results of these calculations seem that thitung greater than ttabel this H1 accepted, meaning the ability of understanding mathematical concepts taught students through cooperative learning model Think Pair share better than the ability of understanding mathematical concepts that students are taught through direct learning model. Keyword : Cooperative learning model Think Pair Share, The ability of understanding mathematical concepts